A study of the impact of salinity on growth and development of important tomato and banana cultivars of the Jordan Valley with an assessment of the efficacy of biostimulants as ameliorants for increased tolerance to salinity - Abu Zurayk, Iad (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University